Implementation of Adaptive Physical Education in Futsal for Children with Mild Intellectual Disabilities at SLB Sumbersari, Bandung City - Wardana, Lalu Teguh; Mastiani, Emay (Journal of English Language and Education, 2025)
This study focuses on adaptive physical education for children with mild intellectual disabilities, particularly through futsal, at SLB C Sumbersari, Bandung. Physical education is often challenging for children with mild intellectual disabilities due to their cognitive and physical limitations. Adaptive physical education is designed to meet their needs, allowing optimal participation in physical activities and sports. The study employed a descriptive qualitative approach, with data collected through observation, interviews, and document analysis. The subjects were physical education teachers and children aged 11 to 17 years with mild intellectual disabilities. Findings suggest that futsal can be effectively played by these children with adjustments to the game’s rules, duration, number of players, and the use of visual and verbal aids. Challenges include limited facilities, varying individual abilities, and the need for teacher training. Solutions include renting futsal fields and providing training for teachers to better teach the sport. In conclusion, adaptive physical education through futsal positively impacts the physical and social development of children with mild intellectual disabilities, leading to success in regional and national events such as O2SN-PDBK and the Special Olympics.